School of Medicine Composite, New Students 1935 (1935)
Duke University School of Medicine, New Students- 1935: Adams, F.M., Jr.; Biddle, R.M.; Brown, W.E.; Bunch, C.P.; Burk, J.M.; Carmichael, G.G.; Cayer, D.; Cox, J.H.; Crosby, F.H.; Douglas, J.M.; Downing, J.R.; Dunlap, E.B.; Eagles, A.Y.; Eckbert, W.F.; Field, A.L.; Haymond, W.V.; Kernodle, H.B.; Kornegay, R.D.; Larsen, C. Jr.; Latchem, C.W.; Lawrence, J.; Lincicome, R.C.; Lucas, P.W.; Mattocks, T.R.; McAnally, W.J., Jr.; HE Merkley; Meyer, F.P.; Moffitt, O.P., Jr.; RC Morrow Jr; Moser, L.A.; Munroe, C.A.; Munson, H.T.E.; Nalle, B.C., Jr.; Newman, G.C.; Nickau, R.H.; Nixon, P.I.; Palen, G.M.; Parrish, A.A.; Pyle, L.A., Jr.; J S Raper; Rysanek, W.J., Jr.; Sawyer, L.E.; Schanher, P.W., Jr.; Schnoor, T.G.; Smith, R.C.; Stark, S.; Storey, W.D.; Surles, D.L.; Thetford, J.D.; Timmons, J.R.; Trachtenberg, W.; Turner, L.; Wadsworth, J.A.C.; Walp, F.M.J.; Watson, G.A., Jr.; Webb, R.C.; Weeks, K.D.; Wexler, J.B.; Wilson, R.A.; Wren, J.C.